2020
DOI: 10.1101/2020.08.11.246314
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

K18-hACE2 mice develop respiratory disease resembling severe COVID-19

Abstract: SARS-CoV-2 emerged in late 2019 and resulted in the ongoing COVID-19 pandemic. Several animal models have been rapidly developed that recapitulate the asymptomatic to moderate disease spectrum. Now, there is a direct need for additional small animal models to study the pathogenesis of severe COVID-19 and for fast-tracked medical countermeasure development. Here, we show that transgenic mice expressing the human SARS-CoV-2 receptor (angiotensin-converting enzyme 2 [hACE2]) under a cytokeratin 18 promoter (K18) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
72
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(92 citation statements)
references
References 45 publications
20
72
0
Order By: Relevance
“…We, and others, detected hACE2 expression predominantly on alveolar epithelial cells, with some expression in bronchiolar epithelial cells following transduction with a dose of 2.5x10 8 PFU Ad-hACE2 (26,56). In this study, we also detected some transduction in endothelial cells and alveolar macrophages, which is consistent with the known in vivo cellular tropism for Ad vectors based on HAdV-C5 in mice (30,33,40).The K18-hACE2 transgenic model has been well characterized for SARS-CoV-1 (20,35), but until more recently had not been comprehensively for SARS-CoV-2 infection, in terms of measuring morbidity and viral dissemination with subsequent replication in extra-pulmonary organs (41,58). In this study, we wanted to perform a head-tohead comparison of the K18-hACE2 model and the Ad-hACE2 murine model in supporting SARS-CoV-2 viral replication in both BALB/c and B6 mice in parallel.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…We, and others, detected hACE2 expression predominantly on alveolar epithelial cells, with some expression in bronchiolar epithelial cells following transduction with a dose of 2.5x10 8 PFU Ad-hACE2 (26,56). In this study, we also detected some transduction in endothelial cells and alveolar macrophages, which is consistent with the known in vivo cellular tropism for Ad vectors based on HAdV-C5 in mice (30,33,40).The K18-hACE2 transgenic model has been well characterized for SARS-CoV-1 (20,35), but until more recently had not been comprehensively for SARS-CoV-2 infection, in terms of measuring morbidity and viral dissemination with subsequent replication in extra-pulmonary organs (41,58). In this study, we wanted to perform a head-tohead comparison of the K18-hACE2 model and the Ad-hACE2 murine model in supporting SARS-CoV-2 viral replication in both BALB/c and B6 mice in parallel.…”
Section: Discussionsupporting
confidence: 85%
“…The brains of K18-hACE2 mice on D5 and D6 had strong red (Nova Red) labelling of neuronal cytoplasm within the cerebral cortex, which included strong labelling of the cell bodies as well as the dendrites and axons (Fig.4D). The timing of N expression in the brain is consistent with other studies which observed little expression prior to D3 post-challenge, but increased staining after D3 (41). Sections of tissues imaged at 20X magnification are shown in Supplementary.Fig.2.…”
Section: Pathologysupporting
confidence: 87%
See 3 more Smart Citations